AN INVESTIGATION OF TPACK WITHIN ICT INTEGRATION: THE CASE OF NON-CERTIFIED ENGLISH TEACHERS IN KOLAKA - Kusuma, Vinsensius Galuh; Saputra, Wiwin; Surianti, Andi; Margana, Margana (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
This study focuses on non-certified English teachers using Information and Communication Technology (UICT) in the teaching practice with the framework is technological pedagogical and content knowledge (TPACK). The purpose is to elaborate on the interrelationship between all TPACK components and their roles in predicting UICT based on the beliefs of the teachers during teaching practice. The researchers used a mixed-methods design for 20 participants from SMP IT Nur Syamzam Kolaka. Questionnaire and interview, especially semi-structured interviews as an instrument for this study. To collect the data, the researcher did online with the non-certified English teachers at SMP IT Nur Syamzam Kolaka. Using Pearson's correlation coefficient, the relationship between the application of TPACK and the availability of ICT tools was determined by correlating the overall TPACK result with the adequacy of ICT tools. Therefore, the findings of the study that were obtained through the TPACK survey demonstrate how they effectively apply their knowledge. The teachers demonstrate expert knowledge in all TPACK domains. They demonstrate the highest level of knowledge based on the mean of TK (4.28), followed by CK (4.26). While all areas of TPACK have a mean of 4.10, PCK and TPK have the lowest mean (4.11).